2005
DOI: 10.1111/j.1365-2109.2005.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary carbohydrate level on growth and body composition of juvenile tilapia, Oreochromis niloticusxO. aureus

Abstract: A growth trial was conducted to feed juvenile tilapia (initial weight,9.1 AE 0.1g), Oreochromis niloticus  O. aureus, isonitrogenous diets for 8 weeks. Six diets were formulated containing 29% crude protein from casein and gelatin, 10% crude fat from soybean oil and re¢ned soybean lecithin and varying levels of corn starch ranging from 6% to 46% at increments of 8%, with corresponding energy to protein (E/P) ratios of 35.6, 37.9, 40.2, 42.5, 44.8 and 47.1kJ g À1 . Weight gain (WG), speci¢c growth rate, feed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
57
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 24 publications
20
57
3
1
Order By: Relevance
“…Our results showed that specific growth rate and feed conversion efficiency increased with the elevating dietary carbohydrate levels from 25.61% to 45.31%, and then decreased with further elevation in carbohydrate levels from 45.31% to 66.09%, suggesting that excess carbohydrate level led to a poor growth of organisms, as reported by other studies (Li et al, 2013;Tan et al, 2009;Wang et al, 2005) EAA, essential amino acid; 2 FAA, flavor amino acid; 3 DAA, drug amino acid; TAA, total amino acid. Seo et al (2011a) with dietary carbohydrate levels from approximately 40% to 70%.…”
Section: Discussionsupporting
confidence: 70%
“…Our results showed that specific growth rate and feed conversion efficiency increased with the elevating dietary carbohydrate levels from 25.61% to 45.31%, and then decreased with further elevation in carbohydrate levels from 45.31% to 66.09%, suggesting that excess carbohydrate level led to a poor growth of organisms, as reported by other studies (Li et al, 2013;Tan et al, 2009;Wang et al, 2005) EAA, essential amino acid; 2 FAA, flavor amino acid; 3 DAA, drug amino acid; TAA, total amino acid. Seo et al (2011a) with dietary carbohydrate levels from approximately 40% to 70%.…”
Section: Discussionsupporting
confidence: 70%
“…This indicated that excess digestible dietary carbohydrate in diets D40 and D 47 to some extent was converted to lipid in various tissues. These increments in tissue lipid due to high starch levels were also reported in previous studies (Rainbow trout, Oncorhynchus mykiss: Tekinay and Davies 2001; Hybrid tilapia, Oreochromis niloticus 9 O. aureus: Wang et al 2005). Moreover, the inclusion of excess energy in diets is known to produce fatty fish, reduce feed consumption and inhibit proper utilization of other feedstuffs (Takeda et al 1975;Shiau and Lin 1993;Ovie et al 2005).…”
Section: Discussionsupporting
confidence: 58%
“…Part of challenges to be solved by the research on fish nutrition is to find mechanisms to diminish protein levels in diets by replacing them with cheaper non-protein energy sources like carbohydrates and lipids (Gao et al 2011). Although finfish do not require carbohydrates in their diet, absence of carbohydrates in diet significantly reduces growth and daily weight gain due to muscle mass loss (Perag on et al 1999) and the incorporation of complex carbohydrates in fish feeding has also been identified to decrease ammonia excretion, improve fish growth and spare protein in many fish species (Shiau & Cheng 1999;Peres & Oliva-Teles 2002;Wang et al 2005;Wu et al 2007). The ability of fish to use dietary carbohydrates differs among species (NRC 2011); diets with high levels of carbohydrates in carnivorous fish diminish consumption of food and their growth (Hemre et al 2002), whereas omnivorous fish are more tolerant to carbohydrates using them more efficiently as energy source and even storing them as lipids (Shiau 1997).…”
Section: Introductionmentioning
confidence: 99%